Spreads of bonds issued by sub-sovereign European governments - Nicolas Jannone Bellot; Maria Luisa Martí Selva; Leandro García Menéndez (Journal of Innovation & Knowledge (JIK), 2017)
This paper identifies the factors that affect the primary and secondary market spreads of fixed and variable rate bonds issued by sub-sovereign European governments. The two markets were analyzed separately to compare whether the factors for the primary market coincided with those for the secondary market. Data for the period between February 2008 and December 2013 were analyzed using panel data estimation. The two markets behaved almost identically, and the signs of the variables were as expected in nearly every case. The most important factor determining the spread of sub-sovereign bonds was the spread of the sovereign bond.
Keywords: G12; G15; G18; 650; Bond spreads; Primary market; Secondary market; Panel data